قواعد ضبط النشاط السياحي لوكالات السياحة والأسفار في التشريع الجزائري - محمودي, مليكة; بخالد, عجالي (جامعة الوادي University of Eloued, 2019)
تزايد في السنوات الأخيرة حجم الاستثمارات المرتبطة بالنشاط السياحي، إلى حد جعل السياحة قاطرة للتنمية في الدول المتقدمة. وقد فرضت وكالات السياحة والأسفار نفسها كأداة فعالة لتنفيذ النشاط السياحي لتشكل صناعة العصر التي ستقود العالم مستقبلا. ونظرا أن النشاط السياحي يمثل تزاوجا بين عالمي الاقتصاد والقانون، فإن وضع الآليات القانونية لضبط هذا النشاط أصبح أولوية تشريعية أكثر من أي وقت مضى. فإذا أريد للنشاط السياحي أن يحقق التنمية فلا بد من وضع قواعد قانونية لضبه بجعله نشاطا مقننا يراعى من خلاله حماية السائح ويحقق غايته الشرعية من جهة، ويحقق التنمية الاقتصادية من جهة أخرى. In recent years, the volume of tourism related to the investment has increased where the tourism become the driver of development in developed countries. Tourist and travel agencies have established themselves as an effective tool for implementing tourism activity to build the industry of the era that will dominate the world in the future. Since tourism is a mixture between economic and law fields, the development of legal mechanisms to control this activity has become a legislative priority more than ever. If tourism activity is to develop, it is necessary to establish legal rules to make it a regulated activity that takes into account the protection of tourists and achieves its legitimate objective on the one hand, and achieves economic development on the other one.
Rules Regulating The Tourism Activity Of Tourist Agencies And Travel In Algerian Legislation
Keywords: النشاط السياحي، وكالة السياحة والأسفار، الترخيص، العقوبات الإدارية، العقوبات الجزائية; Tourism activity, tourist agencies and travel, license, Administrative sanctions, Penal sanctions